1960
DOI: 10.1001/jama.1960.63020020001008
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Necrosis Due to Administration of Metaraminol

Abstract: The use of sympathomimetic amines, such as arterenol (Levophed) bitartrate and metaraminol (Aramine) bitartrate, as vasopressor agents in the treatment of clinical hypotension has received widespread acceptance. The occurrence of ischemic necrosis secondary to the administration of arterenol has been well documented.1 Due to the physiological similarity of these drugs it could be expected that such a complication would arise with extensive use of metaraminol. One such case was reported recently.2 The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…14 However, metaraminol is a potent sympathomimetic amine that has a similar mechanism of action to noradrenaline, 8 and the ability for metaraminol to cause extravasation injury has been documented. 16,32,33 A recent systematic review investigating the safety of peripheral vasopressors concluded vasopressor extravasation was low (3.4%) and was associated with a low rate of major complications. 16 However, the studies investigating metaraminol did not report extravasation rates.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, metaraminol is a potent sympathomimetic amine that has a similar mechanism of action to noradrenaline, 8 and the ability for metaraminol to cause extravasation injury has been documented. 16,32,33 A recent systematic review investigating the safety of peripheral vasopressors concluded vasopressor extravasation was low (3.4%) and was associated with a low rate of major complications. 16 However, the studies investigating metaraminol did not report extravasation rates.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines suggest the addition of vasopressin or epinephrine as secondary vasopressors to increase mean arterial pressure (MAP) to target values or to decrease the consumption of norepinephrine 1. In some parts of the world, secondary vasopressor selection includes the use of metaraminol, which is a vasopressor that has been available for more than 50 years 5. Metaraminol is a sympathomimetic amine that causes vasoconstriction via a direct effect on α 1 adrenergic receptors and indirectly via release of norepinephrine by sympathetic nerve endings 6.…”
Section: Introductionmentioning
confidence: 99%
“…Metaraminol is an inotropic vasoconstrictor, which has the desirable effect of increasing renal blood flow,8 however, it may produce arrhythmias 9. 1 and has been reported to cause local slough when there has been extravascular infiltration of the drug.ii , 12 Norepinephrine has for some years been the vasopressor of choice in combating cardiogenic shock. The advent of this substance first truly increased the recovery rate in cardiogenic shock, dropping the mortality rate from 80 to 47.8 per cent.…”
mentioning
confidence: 99%